PEMAKNAAN STANDAR KECANTIKAN PADA REMAJA PEREMPUAN SURABAYA (STUDI ANALISIS RESEPSI FILM IMPERFECT) (Universitas Negeri Surabaya, 2022)
In the era of information disclosure, films are one of the shows that are in great demand by various groups, ranging from teenagers to the elderly. There are many discussions about social issues, one of which is the standard of beauty in society. One of the films that raises the standard of beauty in Indonesia is Film Imperfect. This study uses Stuart Hall's reception theory. This theory explains how a show affects the audience so that it can be categorized into three parts of the audience, namely Hegemony, Negotiation, and Opposition. This study uses a qualitative approach, constructivism paradigm, and in-method depth interview. The informants taken in this study were six people from three schools with details of two private schools and one public school. Interviews were conducted online by asking open-ended questions to ensure that the informants were included in the reception audience. The results of this study indicate that film shows still significantly affect the audience in terms of support such as the background of the informant and the social life of the informant in accordance with Stuart Hall's theory. Results The meaning of Surabaya's adolescent beauty standards is still very high, this can be seen in the arguments of the informants of this study that beauty standards are still driven in one's physical view. A thin body indicates that a teenager at his age will get an easy job when he graduates from high school. Clean white skin indicates that teenagers at their age look to take care of themselves and deserve more attention from their environment. Straight hair indicates that they get lucky genes so that their appearance can be used as a reference to build friendship relationships and inner beauty is one of the things that is taken into consideration in establishing a friendship relationship. Keywords:Film Imperfect, Reception, Beauty Standard.